ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT PENDAPATAN PETANI PADI DI DESA PONE - Yuwin Ali; siskawati latawa (JSAP : Journal Syariah and Accounting Public, 2018)
This study aims to obtain an overview of the factors that influence the income level of rice farmers. The research method uses a quantitative type. The results of the study simultaneously (F test) there is a positive and significant effect of variable land area, selling price and production amount on farmer income, meaning that the height of land area, selling price and production affect the high and low income of lowland rice farmers